Synergistic Effects of Salicylic Acid, Hydrogel, and Sulphur Sources for Boosting the Yield of Rapeseed under Limited Irrigation - Palvi Dogra; Ankita Thakur; Sarvjeet Kukreja; Alanoud T. Alfagham; Rajeev Kumar Gupta; Meraj Ahmad; Yogesh Dahiya; Manzer H. Siddiqui; Saud Alamri (BioResources)
Preserving global rapeseed production against water shortages requires innovative strategies to enhance crop resistance. Despite its importance, rapeseed remains a water-intensive crop, making traditional irrigation practices unsustainable. Recent studies have explored methods to improve water use efficiency, and this study focuses on applying bioregulators to increase rapeseed yield under water-limited conditions, thereby contributing to food security and sustainability. A field experiment was conducted at the Agricultural Research Farm of Lovely Professional University during the 2021–2022 and 2022–2023 rabi seasons. The experiment, arranged in a split-plot design with 24 treatments, involved gypsum, bentonite sulphur, and elemental sulphur as various sulphur sources in main plots and hydrogel (2.5 kg/ha) and salicylic acid (150 ppm) applications at flowering and pod formation stages in subplots treatments. Gypsum (S1) notably seed yield, root length, and root dry weight. Additionally, hydrogel and salicylic acid applied during 50% flowering and 50% pod development (A6) produced the highest seed yield, root length, and root dry weight. This treatment also enhanced siliqua length and seed count, indicating the potential of gypsum and bioregulators in improving Brassica napus L. production under water-limited conditions.